Propuesta arquitectónica para un centro de resocialización de delincuentes menores (Pitalito-Huila) (2020)
Generate possible solutions to the different problems faced by the Colombian justice system, within the branch of the prison system, focused on the impact and consequences that prison overcrowding generates for the process of resocialization of an individual, taking as a starting point the Pitalito municipality jail or EPMSC 142, through architectural and urban proposals that cover different scales, including macro, meso, micro and the intervention polygon, in order to offer a comprehensive and articulated solution.